2020
DOI: 10.1111/bcp.14211
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac failure in patients treated with azacitidine, a pyrimidine analogue: Case reports and disproportionality analyses in Vigibase

Abstract: Aims: Azacitidine (AZA), a pyrimidine analogue, is validated for high-risk myelodysplastic syndrome or low-blast acute myeloid leukaemia in unfit patients for more intensive treatment. This study assessed the putative link between cardiac failure (CF) and AZA exposure.Methods: Cases of CF in patients treated with AZA were retrospectively collected and described from several centres of the Groupe Francophone des Myélodysplasies. A description analysis and a disproportionality analysis using Vigibase, the WHO Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Taken together with our previous study, that demonstrated that treatment of SHRs with 10 mg/kg 5aza actually lead to improved ejection fraction, these data suggest that treatment with low-dose 5aza may lead to improved cardiac function in the setting of pressure overload. This is important because a recent study identified four oncology cases (out of a database of over 9000 adverse events) where high-dose 5aza treatment was associated with alterations in ejection fraction and temporary symptoms of heart failure [31]. Unfortunately it is impossible to know whether the cardiac events reported were caused by 5aza treatment or related to the ongoing disease process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together with our previous study, that demonstrated that treatment of SHRs with 10 mg/kg 5aza actually lead to improved ejection fraction, these data suggest that treatment with low-dose 5aza may lead to improved cardiac function in the setting of pressure overload. This is important because a recent study identified four oncology cases (out of a database of over 9000 adverse events) where high-dose 5aza treatment was associated with alterations in ejection fraction and temporary symptoms of heart failure [31]. Unfortunately it is impossible to know whether the cardiac events reported were caused by 5aza treatment or related to the ongoing disease process.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because a recent study identified 4 oncology cases (out of a database of over 9000 adverse events) where high-dose 5aza treatment was associated with alterations in ejection fraction and temporary symptoms of heart failure. 31 Unfortunately it is impossible to know whether the cardiac events reported were caused by 5aza treatment or related to the ongoing disease process. For example, myelodysplastic syndromes are associated with a complex array of systemic complications such as chronic anaemia 32 and iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…Spallota et al . also reported a similar observation, who showed that 5mC and its oxidative intermediate product 5hmC accumulate in cardiac mesenchymal cells isolated from T2D patients, cardiac tissue of STZ-induced diabetes and HFD-fed mice [ 19 ]. The current study also demonstrated that the genomic distribution of the 5mC and 5hmC peaks was significantly enriched in gene body regions, particularly in intronic regions (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…While the use of different epigenetic modulators, such as cytidine analogs 5-azacytidine and decitabine, as DNMT inhibitors for cancer treatment, is well documented, the therapeutic potential of these modulators is limited due to their lower stability and cytotoxicity. Additional side effects from treatment with these drugs were also reported in cancer patients with other comorbidities, such as T2D or cardiac disorders [ 16 19 ]. Moreover, the use of non-nucleoside analogs such as hydralazine and procainamide is also limited because of their specificity for DNMT1 and side effects such as autoimmune diseases [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other serious AEs detected included TLS, organizing pneumonia, and cardiac failure signals. These AEs did not differ in frequency from those of the target drug in clinical trials and were reported only on a case-report basis, with only a few reports in Japanese patients [4649]. TLS often develops early in the course of treatment and follows a lethal course; this study suggested that it occurs within about 1 week of treatment.…”
Section: Discussionmentioning
confidence: 65%